Is the isolation of people living with HIV/AIDS in Mogalakwena, Waterberg district hospitals aggravating stigma and discrimination against people living with HIV/AIDS? - Mokwena, William Oukie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.